Influence of Germany and Japan in 21st Century: Liberalism or Realism - Zaidi, Syed Ahsan Raza (Journal of Nautical Eye and Strategic Studies, 2023)
Military power is the most effective instrument in pursuing policy of hegemony and influence in the region, continent and world. In contrary Germany and Japan have been able to create strong influence in continental and world affairs an example is the presence of Germany in JCPOA 2015 despite exercising restraint on military arm. The industrial and economic growth of these countries has made them power center in Asia and Europe respectively. This situation creates a unique situation where Liberalism has been crucial in catapulting the two nations from ignominy of defeat to continental and world power broker. A question is raised for proprietors of Realism who advocate use of military instrument to gain power or influence. Germany and Japan’s pursuing of non-belligerent, trade oriented and public diplomacy practicing foreign policy is implementation of Liberalism in 21st Century or another form of Realism. Focus on relevant aspects of Realism and Liberalism will assist in linking these theories with foreign policy of the two countries. This paper will highlight the cardinal of Germany and Japan’s foreign policy after WW2. The role of Germany and Japan in UNO and other regional and international organizations will also be studied.